A sequential two-stage dose escalation study of eltrombopag in patients with myelodysplastic syndrome and thrombocytopenia after hypomethylating agent failure. Issue 8 (2nd July 2020) - Duong, Vu H.; Al Ali, Najla; Zhang, Ling; Padron, Eric; Sallman, David; Lancet, Jeffrey E.; List, Alan F.; Komrokji, Rami S.
Abstract: Thrombocytopenia occurs frequently in patients with myelodysplastic syndromes (MDS), and the survival of patients after failure of hypomethylating agents (HMAs) is poor. We conducted a trial of eltrombopag in patients with MDS, MDS/myeloproliferative neoplasm (MPN) or acute myeloid leukemia (AML) with 20–30% myeloblasts after HMA failure and mean baseline platelet count ≤ 50 × 10 9 /L. Eltrombopag was escalated from 50 mg daily up to 200 mg daily. The primary objective was to determine the maximally tolerated dose (MTD). 37 patients were enrolled, and MTD was not reached. Responses were observed in 9 patients (24%), 2 achieving marrow CR with hematologic improvement (HI), 1 marrow CR without HI, and 6 HI. Median overall survival was 7.5 months. Eltrombopag was well-tolerated and yielded modest responses in heavily treated, predominantly higher-risk MDS patients after HMA failure. Future studies should focus on determining characteristics that predict response.